Elucidation of the temporal relationship between endothelial-derived NO and EDHF in mesenteric vessels. - Harrington, L; Carrier, M; Gallagher, N; Gilroy, D; Garland, C; Mitchell, J (2007)
Although the endothelium co-generates both nitric oxide (NO) and endothelium-derived hyperpolarizing factor (EDHF), the relative contribution from each vasodilator is not clear. In studies where the endothelium is stimulated acutely, EDHF responses predominate in small arteries. However, the temporal relationship between endothelial-derived NO and EDHF over more prolonged periods is unclear but of major physiological importance. Here we have used a classical pharmacological approach to show that EDHF is released transiently compared with NO. Acetylcholine (3 x 10(-6) mol/l) dilated second- and/or third-order mesenteric arteries for prolonged periods of up to 1 h, an effect that was reversed fully and immediately by the subsequent addition of L-NAME (10(-3) mol/l) but not TRAM-34 (10(-6) mol/l) plus apamin (5 x 10(-7) mol/l). When vessels were pretreated with L-NAME, acetylcholine induced relatively transient dilator responses (declining over approximately 5 min), and vessels were sensitive to TRAM-34 plus apamin. When measured in parallel, the dilator effects of acetylcholine outlasted the smooth muscle hyperpolarization. However, in the presence of L-NAME, vasodilatation and hyperpolarization followed an identical time course. In vessels from NOSIII(-/-) mice, acetylcholine induced small but detectable dilator responses that were transient in duration and blocked by TRAM-34 plus apamin. EDHF responses in these mouse arteries were inhibited by an intracellular calcium blocker, TMB-8, and the phospholipase A(2) inhibitor AACOCF(3), suggesting a role for lipid metabolites. These data show for the first time that EDHF is released transiently, whereas endothelial-derived NO is released in a sustained manner.